Define the functional organization of cerebellar output circuits that control cognitive behavior - Tan, Shaun (Nanyang Technological University, 2020)
The cerebello-thalamo-cortical circuit which connects the prefrontal cortex (PFC) and the cerebellum has been implicated in the working memory (WM). However, the exact involvement of the PFC and the cerebellum in this context has been unclear. In this study, we examined the neural functions in the PFC and the cerebellum using in vivo calcium imaging during two different WM-engaging tasks. Delay activity in the dorsomedial prefrontal cortex (dmPFC) neurons was observed and was central in modulating the maintenance of the WM. These trial-dependent neurons were found to contain directional preference and translate to the bias observed during the delayed-task. Furthermore, changes in stimuli modality were perceived to affect the directional preference, causing the neurons to increase its dynamicity. Such properties were discovered to negatively correlate with the performance of the delayed-task, highlighting the importance of the preferential trial-dependent neurons. Although simultaneous PFC and deep cerebellar nuclei (DCN) imaging were unsuccessful, delay-like activity was observed from the background fluorescence in the cerebellum, suggesting the viability of such an approach. Thus, the findings from this study would serve as an attempt to facilitate future studies involving the dmPFC and the DCN in elucidating their respective roles in the WM.